Would a competitive real exchange rate be a driver of economic prosperity? - Iasco-Pereira, Hugo; Missio, Fabrício José (PSL Quarterly Review, 2023)
This article assesses the effects of real exchange rate misalignment on long-term growth, between 1995 and 2018, in a set of 151 countries. Our findings indicate that a competitive real exchange rate is positively associated with growth over the long run. The novel element here is our demonstration that the enhanced international competitiveness generated by lower labor costs may increase growth. The study also includes a series of robustness checks and alternative estimates to better understand this association, using seven different measures of real exchange rate misalignment, controlling for the possibility that the real exchange rate has a non-monotonic effect on growth, testing the Washington Consensus, separately estimating the effects of real exchange rate devaluation and overvaluation, testing the argument that a real exchange rate policy is an important factor in explaining why Asian economies perform better than Latin American and African ones, and employing alternative measures for real exchange rate misalignment.